HABITAT UTILIZATION BY ASIATIC WILD ELEPHANT (ELEPHUS MAXIMUS) IN PARSA WILDLIFE RESERVE, NEPAL - Yadav, B. R.; Dutta, I. C.; Chilese, M. K.; Williums, Christy; Sharma, B. K. (Ecoprint: An International Journal of Ecology, 2014)
During the habitat survey, elephants foot prints, dungs and dirct observations were performed alongeach sampling grid. GPS points of elephant's presence were recorded. Aiming to provide quantitativeanalysis of habitats, circular quadrats of 10 m, 2 m and 1m radius were used to collect informationabout trees, shrubs and herbs. Importance values of each species of trees were analyzed by addingrelative frequency, relative density and relative dominance. Name of each forest type was determinedfrom the sequencial order of the large Importance Values (IV) of tree species. Prominance valueswere calculated for shrubs and ground flora and were used for classification of the shrub and groundvegetation type. Higher area of the reserve was covered by the forest (85.9%) followed by agricultureand buildup land (5.1%), grassland (3%), water body (3%), riverbed (2%) and shrub land (1%),respectively. Based on the phyto-sociological combination, forests of this reserve incorporated fourtypes namely Sal with Tarai Mixed Hardwood, Sal, Tarai Mixed Hardwood and Riverine.Ample ofevidence found inside lowler part (Tarai, Bhabar and the base of Churia) of Parsa Wildlife Reserve. Asuitable habitat with palatable forages (eg, Mallotus philippinnesis, Bananas, bamboos and climbers)for wild elephants were found inside the reserve. These forests were used as prime habitat by theAsiatic wild elephant. DOI: http://dx.doi.org/10.3126/eco.v20i0.11440 ECOPRINT An International Journal of Ecology Vol. 20, 2013 Page 41-52